An Integrated Pedagogical Model For Teaching Gymnastics: Biomechanical, Digital And Didactic Foundations - Akimov, Nokisbay (Indonesian Journal Publisher, 2025)
This study examines the effectiveness of three instructional models—traditional demonstration-based teaching, biomechanical segmentation, and digital-assisted instruction—in the acquisition of fundamental gymnastic skills among university students. The research employed a mixed-methods design integrating pedagogical experimentation, biomechanical motion analysis, psychophysiological monitoring, and statistical evaluation over a twelve-week intervention period. A total of 120 physical education students were randomly assigned to experimental groups, each receiving a different instructional modality. Results show that digital-supported instruction significantly accelerated motor learning, improved technical accuracy, enhanced balance stability, and increased strength and flexibility compared to both traditional and biomechanical-only approaches. Learners in the digital group also demonstrated superior error-correction efficiency, reduced fear levels during inverted movements, and higher autonomy in self-regulation. These outcomes align with ecological-dynamics theories of motor learning and confirm the pedagogical value of information-rich learning environments. The findings support the development of an integrated instructional model combining biomechanics, digital feedback technologies, and psychological readiness training. This model is particularly relevant for modernizing physical education systems in resource-limited educational contexts, where affordable digital tools can substantially elevate instructional quality. The study contributes to contemporary sport pedagogy by demonstrating that digital augmentation is not merely a technological enhancement but a transformative pedagogical strategy for gymnastics education.